Microscopic and ultramicroscopic characteristic of heart valves in human - Fedoniuk L.; Semeniuk T.; Bodnar E. (Морфологія, 2014)
Background. Valvular apparatus of the heart is the frequent object of the surgical operations for today. Morphological changes which are happed within valves of the heart at time of cardiac diseases the modern medicine considers on the clinical, instrumental, histological, cytological and ultramicroscopical levels. The cardiac surgeons that make the heart valve replacement using the tissue engineering have the great interest in front of the heart valves. The achievements of the modern medicine are impossible without the fundamental morphological investigations. Objective. To study the morphological features of the cusps of human heart valves on the light and ultramicroscopic levels. Methods. We have reviewed the structure of cusps of 48 heart valves of adults. It was used a light and electron microscopy which enabled us to study the morphology of cusps of atria-ventricular and ventriculo-vascular heart valves. Results. The data indicate that cusps of heart valves are stratified. Layers of cusps are made of different types of fibrous connective tissues. The spongy layer is made of loose connective tissue, the fibrous layer – dense regular connective tissue, ventricular layer – dense irregular connective tissue. The arrangement of these layers in the cusps of atria-ventricular heart valves (in the direction from atrium toward ventricle) is: spongy, fibrous and ventricular. The arrangement of these layers in the cusps of ventricular-vascular heart valves (in the direction from side that is faced to the wall of blood vessel toward the ventricle) is: fibrous, spongy, ventricular. Conclusion. The position of data layers within cusp of atria-ventricular valves differs from position of data layers within ventriculo-vascular valves. These changes of tissue localization correlate to haemodynamic conditions during heart cycle. Citation: Fedoniuk L, Semeniuk T, Bodnar E. [Microscopic and ultramicroscopic characteristic of heart valves in human]. Morphologia. 2014;8(3):67-71. Ukrainian.